Pontic structure, dental restoration system, and dental restoration method

CN122954570APending Publication Date: 2026-10-23SHANGHAI SUCHENG DENTURE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611353317.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0004]本发明解决的技术问题在于,现有固定桥修复结构在承受咬合载荷时,刚度分布单一,缺乏有效的受控变形与应力缓冲机制,易导致刚性桥体底层对局部牙槽嵴黏膜产生过大压迫;

Benefits of technology

1、本发明通过在桥体单元内部设置A区六边形蜂窝晶格、B区四面体晶格和C区双尺度混合晶格形成梯度刚度承载结构,能够在承受咬合载荷时使桥体单元中央区域产生受控挠曲,并将载荷合理分配传递至两端的固位体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122954570A_ABST
    Figure CN122954570A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of oral cavity restoration, and discloses a pontic structure, a tooth restoration system and an oral cavity restoration method, which comprise a retainer and a pontic unit; the pontic unit is provided with an A-zone hexagonal honeycomb lattice and a B-zone tetrahedral lattice at two ends, a C-zone double-scale mixed lattice and an internal airflow channel in the center; the pontic unit is provided with a main channel and a branch channel, a three-dimensional anatomical adaptive bottom surface, a longitudinal groove and a through-hole array are arranged at the lower end; a flexible transition layer with a transition layer hole is arranged below the bottom surface, each channel and hole are communicated to form a sealed chamber and encapsulate a non-Newtonian shear thinning fluid. Controlled flexure and occlusal load distribution are realized through the gradient lattice structure, the fluid shear thinning characteristics are used to shunt and push the flexible layer to produce micro-deformation in the chamber to disperse local pressure, the reciprocating flow of gas in the airflow channel is used to dissipate vibration energy, and stress concentration of soft tissue is reduced and long-term stability of the structure is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of oral restoration technology, specifically to bridging structures, tooth restoration systems, and oral restoration methods. Background Technology

[0002] In tooth replacement surgery, fixed bridges are often manufactured using zirconia or other ceramic materials, resulting in a highly rigid solid structure. However, during prolonged chewing, this rigid structure cannot adapt to the complex occlusal environment by undergoing adaptive flexural deformation. When the bridge surface bears occlusal loads, the rigid structure directly transmits the pressure to the base, causing localized stress concentration between the bridge's base and the alveolar ridge mucosa. This continuous mechanical pressure can easily lead to soft tissue damage and resorption of the underlying alveolar bone.

[0003] Meanwhile, conventional rigid solid restorative structures lack dissipation and buffering mechanisms for occlusal impact energy. When chewing hard objects or experiencing transient occlusal impacts, high-frequency vibration loads are transmitted to the abutment teeth on both sides without attenuation, increasing the mechanical burden on the periodontal tissues of the abutment teeth and thus affecting the long-term stability of the restoration and the abutment teeth. In addition, although the existing bridge underside morphology can fit to the mucosa based on scanning data in the early stages of manufacturing, it cannot dynamically disperse and adjust the contact surface pressure at the moment of loading, resulting in an excessive stiffness difference between the rigid bridge body and the soft tissue, making it difficult to achieve a good mechanical fit and protective effect. Summary of the Invention

[0004] The technical problem solved by this invention is that existing fixed bridge restoration structures have a single stiffness distribution when subjected to occlusal loads, lack an effective controlled deformation and stress buffering mechanism, and are prone to excessive pressure on the local alveolar ridge mucosa caused by the bottom layer of the rigid bridge body. Furthermore, existing structures lack effective means of dissipating high-frequency meshing impacts and vibration energy.

[0005] To address the above problems, the present invention provides the following technical solution: The first aspect of the present invention provides a bridge structure, including a retainer and a bridge unit, wherein the retainer is connected to the bridge unit, and the internal structure of the bridge unit is divided sequentially along the mesiodistal direction as follows: The A-region hexagonal honeycomb lattice is located at both ends, the B-region tetrahedral lattice is located in a quarter-span region adjacent to the A-region hexagonal honeycomb lattice, and the C-region dual-scale hybrid lattice is located in the central region. The C-region dual-scale hybrid lattice has multiple airflow channels. The bridge unit is provided with a main road, and three branch roads are provided on each side of the main road. The lower end of the bridge unit is provided with a three-dimensional anatomical adaptation bottom surface. The lower end of the three-dimensional anatomical adaptation bottom surface is provided with a longitudinal groove, and the bottom of the longitudinal groove is provided with an array of through holes. The bottom of the three-dimensional anatomical adapter is provided with a flexible transition layer, and the upper end of the adapter is provided with multiple transition layer holes. The flexible transition layer covers the opening of the longitudinal groove, and the transition layer holes correspond to the positions of the through hole array.

[0006] Furthermore, the through-hole array is connected to the main channel and the branch channel respectively, the lower end of the through-hole array is coaxially connected to the multiple transition layer holes, the retainer is connected to the bridge unit through the hexagonal honeycomb lattice of region A, one end of the main channel forms an injection end, and the injection end is provided with UV sealing adhesive.

[0007] Furthermore, the axes of the plurality of airflow channels are set at an angle to the near-far direction of the bridge body unit, and the airflow channels include a plurality of interconnected cylindrical channel segments, with adjacent cylindrical channel segments connecting at their ends to form a continuously extending airflow path.

[0008] A second aspect of the present invention provides a dental restoration system, including the aforementioned bridging structure, and further including a non-Newtonian shear-thinning fluid. The main channel of the bridging structure, the branch channels of the bridging structure, the through-hole array of the bridging structure, and the transition layer pores of the bridging structure are interconnected to form a closed fluid chamber, and the non-Newtonian shear-thinning fluid is encapsulated inside the closed fluid chamber.

[0009] Furthermore, the flexible transition layer of the bridge structure covers the bottom of the longitudinal groove of the bridge structure. The flexible transition layer is fitted and sealed around the opening of the through hole array and the bottom surface of the longitudinal groove, and the flexible transition layer does not enter the through hole array, the main road and the branch road.

[0010] Furthermore, the non-Newtonian shear thinning fluid is a xanthan gum aqueous solution, the transition layer pores are non-penetrating blind pores, and one end of the transition layer pores away from the bridge body unit of the bridge body structure is closed by the continuous material wall of the flexible transition layer. When the non-Newtonian shear thinning fluid is squeezed, it applies pressure to the continuous material wall, causing the flexible transition layer to undergo micro-deformation.

[0011] The third aspect of the present invention is an oral restoration method applied to the above-mentioned dental restoration system, comprising the following steps: Acquire patient data and establish a three-dimensional oral model to determine the morphology of the retainer, pontoon unit and the three-dimensional anatomical adapter bottom surface, and establish a longitudinal groove in the three-dimensional anatomical adapter bottom surface; Within the bridge unit, a hexagonal honeycomb lattice in region A, a tetrahedral lattice in region B, and a dual-scale hybrid lattice in region C are divided and established. Within the dual-scale hybrid lattice in region C, a sacrificial channel model corresponding to the airflow channel is established. A main channel, branch channels, and through-hole array are established at the bottom of the longitudinal groove, with one end of the main channel forming an injection end; The retainer, the bridge unit, and the sacrificial channel model are manufactured using additive manufacturing equipment. After dissolving and removing the sacrificial material from the sacrificial channel model, the airflow channel is formed through degreasing and sintering. A flexible transition layer and transition layer holes on its surface are manufactured, and the flexible transition layer is covered and fixed to the longitudinal groove, so that the through hole array is connected to the transition layer holes; Non-Newtonian shear-thinning fluid is injected into a closed fluid chamber composed of the main channel, the branch channel, the through-hole array, and the transition layer pores through the injection end, and then sealed.

[0012] Furthermore, in the steps of manufacturing the retainer, the bridging unit, and the sacrificial channel model, the retainer, the bridging unit, the hexagonal honeycomb lattice of region A, the tetrahedral lattice of region B, and the dual-scale mixed lattice of region C are manufactured using ceramic slurry. The sacrificial channel model corresponding to the airflow channel is manufactured using water-soluble material, and the airflow channel is formed by dissolving and discharging the water-soluble material through water injection.

[0013] Furthermore, in the step of manufacturing the flexible transition layer, the flexible transition layer is printed using TPU-based photosensitive resin, and an incompletely cured TPU-based photosensitive resin is coated on the connection area between the bridge unit and the flexible transition layer. The flexible transition layer and the bridge unit are fixed by curing with ultraviolet light.

[0014] Furthermore, in the step of injecting the non-Newtonian shear thinning fluid, before injecting the non-Newtonian shear thinning fluid, the sealed fluid chamber is first evacuated to a set negative pressure state through the injection end reserved in the main channel and pressure is maintained. Then, the non-Newtonian shear thinning fluid is drawn into the sealed fluid chamber by the negative pressure inside the chamber.

[0015] In summary, the present invention has at least one of the following beneficial technical effects: 1. The present invention forms a gradient stiffness bearing structure by setting a hexagonal honeycomb lattice in region A, a tetrahedral lattice in region B, and a dual-scale hybrid lattice in region C inside the bridge body unit. This structure can generate controlled deflection in the central region of the bridge body unit when subjected to interlocking loads and rationally distribute and transfer the load to the retaining bodies at both ends.

[0016] 2. This invention constructs a sealed fluid chamber by means of a main channel, branch channels, an array of through holes, and transition layer holes, and encapsulates a non-Newtonian shear-thinned fluid. By utilizing the characteristics of increased fluid shear rate and decreased apparent viscosity caused by the deformation of the bridge body under load, the fluid is diverted within the chamber and drives the flexible transition layer to produce micro-deformation, thereby dispersing the local contact pressure to the periphery and effectively reducing the stress concentration phenomenon of the bottom of the structure on the mucosal tissue.

[0017] 3. By setting multiple interconnected airflow channels inside the dual-scale hybrid lattice in the C region, the present invention can improve the structural stability of the restoration under dynamic loading conditions by utilizing the periodic compression, expansion and reciprocating flow of the gas in the channels when the interlocking impact vibration is transmitted to the central region of the bridge body. This is achieved through the viscous friction between the airflow and the channel wall and heat exchange to consume part of the vibration energy. Attached Figure Description

[0018] Figure 1 This is a three-dimensional structural diagram of the present invention; Figure 2 This is a longitudinal sectional front view of the present invention; Figure 3 for Figure 2 Enlarged diagram of point A in the diagram; Figure 4 This is a schematic diagram of the through-hole array of the present invention; Figure 5 This is a schematic diagram of the branch channel of the present invention; Figure 6 This is a flowchart illustrating the oral restoration method of the present invention.

[0019] Among them, 1. Stabilizer; 2. Bridge unit; 3. Three-dimensional anatomical adaptation bottom surface; 4. Longitudinal groove; 5. Hexagonal honeycomb lattice in region A; 6. Tetrahedral lattice in region B; 7. Dual-scale hybrid lattice in region C; 8. Airflow channel; 9. Main channel; 10. Branch channel; 11. Through-hole array; 12. Flexible transition layer; 13. Transition layer pores; 14. UV sealing adhesive. Detailed Implementation

[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] See attached document Figure 1 and attached Figure 2This embodiment provides a pontoon structure, including retainers 1 and pontoon units 2. Two retainers 1 are provided, located at the mesial and distal ends of the pontoon unit 2 respectively, for connection to the abutment teeth on both sides of the edentulous region. The pontoon unit 2 is located between the two retainers 1, spanning the edentulous region and bearing occlusal loads. After the occlusal load is applied to the pontoon unit 2, it is transmitted to both ends through the load-bearing structure inside the pontoon unit 2, and then transmitted to the corresponding abutment teeth by the retainers 1.

[0022] See attached document Figure 4 The lower end of the pontoon unit 2 is provided with a three-dimensional anatomical fitting bottom surface 3. The three-dimensional anatomical fitting bottom surface 3 is established based on the patient's intraoral scan data and cone-beam computed tomography scan data, and its contour is adapted to the patient's alveolar ridge crest line and the buccal and lingual mucosal transition positions.

[0023] The 3D anatomical adapter base surface 3 is modeled simultaneously along the mesiodistal and buccal-lingual directions of the alveolar ridge. The buccal, lingual, and mesiodistal edges of the 3D anatomical adapter base surface 3 all feature rounded transitions with radii of curvature ranging from 0.3 mm to 0.8 mm to reduce localized stress concentration on the alveolar ridge mucosa in the marginal areas. The central contact area of ​​the 3D anatomical adapter base surface 3 is established according to the actual morphology of the patient's alveolar ridge mucosal surface.

[0024] The central region of the three-dimensional anatomical adapter bottom surface 3 has a longitudinal groove 4 that is recessed into the bridging unit 2. The longitudinal groove 4 extends along the mesiodistal direction of the alveolar ridge, with a width of 1.2mm to 1.8mm and a depth of 0.15mm to 0.25mm. The bottom of the longitudinal groove 4 is rounded. The longitudinal groove 4 reduces the rigidity of the local structure at the bottom of the bridging unit 2 on the one hand, and provides space for the arrangement of the microchannel network on the other.

[0025] The proximal and distal ends of the longitudinal groove 4 terminate on the inner side of the corresponding retainer 1 and do not extend into the interior of the retainer 1. The opening of the longitudinal groove 4 faces the alveolar ridge mucosa.

[0026] Combined with appendix Figure 2 The internal structure of bridge unit 2 is divided into the following sections along the near-far-center direction: hexagonal honeycomb lattice 5 in region A at both ends, tetrahedral lattice 6 in region B with a quarter span adjacent to hexagonal honeycomb lattice 5 in region A, and dual-scale hybrid lattice 7 in region C in the central region.

[0027] The hexagonal honeycomb lattice 5 in region A is disposed on the near-middle and far-middle sides of the bridge unit 2, respectively located in the connection region between the corresponding retainer 1 and the bridge unit 2. The span division of region B and region C inside the bridge unit 2 is not taken into account for the hexagonal honeycomb lattice 5 in region A.

[0028] The hexagonal honeycomb lattice 5 in region A has a filling density of 85%–92% and a cell side length of 0.35 mm. The hexagonal honeycomb lattice 5 in region A is used to improve the structural stiffness of the connection area and to transfer the load borne by the bridge unit 2 to the retainer 1.

[0029] The hexagonal honeycomb lattice 5 in region A is interconnected with each other. One side of the hexagonal honeycomb lattice 5 in region A is continuously connected to the retainer 1, and the other side is continuously connected to the corresponding tetrahedral lattice 6 in region B.

[0030] Two B-region tetrahedral lattices 6 are respectively disposed in the near-middle quarter-span region and the far-middle quarter-span region of the bridge unit 2. The filling density of the B-region tetrahedral lattices 6 is 65% to 75%. The cell edge length gradually decreases from 0.45 mm near the A-region hexagonal honeycomb lattice 5 to 0.3 mm towards the center of the bridge unit 2.

[0031] The structural filling density of the tetrahedral lattice 6 in region B gradually decreases from 75% on the side closer to the hexagonal honeycomb lattice 5 in region A to 65% on the side closer to the dual-scale hybrid lattice 7 in region C. By adjusting the cell edge length and structural filling density, the equivalent stiffness of the tetrahedral lattice 6 in region B gradually decreases from region A to region C.

[0032] A C-region dual-scale hybrid lattice 7 is set in the central half-span region of bridge unit 2. The filling density of the C-region dual-scale hybrid lattice 7 is 40% to 50%, and its principal lattice adopts a regular dodecahedral framework with a cell side length of 0.6 mm.

[0033] An array of spherical cavities with a diameter of 0.12 mm is set inside the dodecahedral framework. The total volume of the spherical cavities accounts for 38% ± 3% of the total volume of the C-region dual-scale hybrid lattice 7. The filling density of the C-region dual-scale hybrid lattice 7 refers to the proportion of the ceramic solid volume to the envelope volume of the C-region after setting the array of spherical cavities.

[0034] The hexagonal honeycomb lattice 5 in region A, the tetrahedral lattice 6 in region B, and the dual-scale hybrid lattice 7 in region C together constitute a gradient stiffness load-bearing structure. The stiffness of this structure gradually decreases from both ends of the bridge structure towards the center of bridge unit 2.

[0035] The hexagonal honeycomb lattice 5 in region A, the tetrahedral lattice 6 in region B, and the dual-scale hybrid lattice 7 in region C are continuously connected in adjacent regions, and there are no broken lattice members between adjacent regions. Region A is used to support the fixed connection area, region B is used to realize the stiffness transition, and region C is used to reserve controlled deformation space for the central region of bridge unit 2.

[0036] Multiple airflow channels 8 are provided inside the C-region dual-scale hybrid lattice 7. The airflow channels 8 are through channels with a diameter of 0.2 mm, and their axes form a 7° angle with the near-far-mid span direction of the bridge unit 2. The minimum ceramic wall thickness between the airflow channels 8 and the adjacent lattice entities is 0.05 mm.

[0037] The center-to-center distance between adjacent airflow channels 8 is 1.08 mm, and they are offset by 0.1 mm in the height direction of bridge unit 2. The airflow channels 8 are deviated from the extension direction of the main load-bearing lattice members to reduce the impact of the channel arrangement on the main load-bearing cross section.

[0038] The airflow channel 8 comprises multiple interconnected cylindrical channel segments. Adjacent cylindrical channel segments are connected at their ends, so that multiple airflow channels 8 form an airflow pathway that extends continuously along the near-to-far-center direction within the C-region dual-scale hybrid lattice 7.

[0039] The sacrificial channel corresponding to the airflow channel 8 extends to the lingual non-occlusal surface of the bridge unit 2 at the proximal and distal ends, respectively, forming a cleaning inlet and a cleaning outlet. The cleaning inlet is used to allow deionized water to enter the sacrificial channel, and the cleaning outlet is used to discharge the dissolved PVA material.

[0040] After the sacrificial material is removed and the bridge body green body is degreased and sintered, UV sealing glue 14 is used to seal the cleaning inlet and cleaning outlet, so that the airflow channel 8 is isolated from the oral cavity environment.

[0041] When the meshing vibration is transmitted to the C-region dual-scale mixed lattice 7, the gas in the gas flow channel 8 undergoes compression, expansion, and reciprocating flow. During the gas movement, some vibrational energy is consumed through viscous friction between the gas and the inner wall of the channel, gas compression hysteresis, and heat exchange between the gas and the channel wall.

[0042] See attached document Figure 5 The bottom of the longitudinal groove 4 is provided with a main channel 9. The main channel 9 extends along the center line of the longitudinal groove 4, with a width of 0.22 mm and a depth of 0.18 mm.

[0043] Three branch lanes 10 are provided on each side of the main road 9, forming a total of six branch lanes 10. Each branch lane 10 has a width of 0.12 mm and a depth of 0.15 mm. The main axis of the branch lane 10 forms a 15° angle with the main axis of the main road 9 and extends obliquely to the side of the longitudinal groove 4.

[0044] Six branch channels 10 are symmetrically distributed on both sides of the main channel 9. One end of each branch channel 10 connects to the main channel 9, and the other end terminates in the buccal or lingual edge region of the longitudinal groove 4. The ends of the branch channels 10 are closed by the solid material of the pontoon unit 2 and do not communicate with the oral environment.

[0045] The main channel 9 and the six branch channels 10 together form a branched microchannel network. The total projected area of ​​the main channel 9 and the six branch channels 10 on the bottom plane of the longitudinal groove 4 accounts for 28% to 35% of the projected area of ​​the bottom of the longitudinal groove 4.

[0046] A through-hole array 11 is formed at the bottom of the longitudinal groove 4. Each through-hole in the through-hole array 11 extends along the vertical direction of the bridge body unit 2, the diameter of the through-hole is 0.15mm, and the center distance between adjacent through-holes is 0.3mm.

[0047] The through-hole array 11 is connected to the main road 9 and each branch road 10. The end region of each branch road 10 is connected to at least one through-hole.

[0048] See attached document Figure 3 A flexible transition layer 12 is provided at the lower end of the three-dimensional anatomical adapter bottom surface 3. The flexible transition layer 12 is formed by digital light processing additive manufacturing of TPU-based photosensitive resin, with a thickness of 0.18mm to 0.22mm and a Young's modulus of 8MPa to 12MPa.

[0049] The pontoon unit 2 is made of 3Y-TZP zirconia ceramic material with a Young's modulus of 210 GPa. A flexible transition layer 12 is located between the zirconia pontoon unit 2 and the alveolar ridge mucosa. The Young's modulus of the alveolar ridge mucosa is 0.1 MPa to 0.5 MPa; the flexible transition layer 12 is used to reduce the modulus difference between the zirconia pontoon unit 2 and the alveolar ridge mucosa.

[0050] The flexible transition layer 12 adheres to and covers the bottom of the longitudinal groove 4 and its surrounding area. The flexible transition layer 12 adheres to and seals the bottom surface of the longitudinal groove 4 around the opening of the through hole array 11, and the flexible transition layer 12 does not enter the through hole array 11, the main channel 9 and the branch channel 10.

[0051] The flexible transition layer 12 has multiple transition layer holes 13 on the side facing the bridge unit 2. The transition layer holes 13 are non-through blind holes, and their ends away from the bridge unit 2 are closed by the continuous material wall of the flexible transition layer 12. Each transition layer hole 13 corresponds to one through hole in the through hole array 11 and is coaxially connected to the corresponding through hole.

[0052] Fluid in the main channel 9 and branch channels 10 can enter the corresponding transition layer holes 13 through the through hole array 11. The fluid pressure acts on the continuous flexible material wall below the transition layer holes 13, causing the flexible transition layer 12 to undergo elastic micro-deformation toward the alveolar ridge mucosa.

[0053] When the flexible transition layer 12 is connected to the zirconia bridge unit 2, an incompletely cured TPU-based photosensitive resin is coated on the connection area of ​​the zirconia bridge unit 2. Then, the flexible transition layer 12 is positioned on the three-dimensional anatomical adapter bottom surface 3, so that the through-hole array 11 and the transition layer holes 13 are correspondingly connected. Then, the connection area is irradiated with ultraviolet light to cure the TPU-based photosensitive resin, and the flexible transition layer 12 is fixed to the zirconia bridge unit 2.

[0054] A non-Newtonian shear-thinning fluid is encapsulated within a microfluidic network. The non-Newtonian shear-thinning fluid is a 0.8% (w / w) xanthan gum aqueous solution. The static viscosity of the xanthan gum aqueous solution is 1200 mPa·s–1500 mPa·s, and it exhibits a shear rate of 100 s⁻¹. -1 At that time, the viscosity decreased to 320 mPa·s to 380 mPa·s.

[0055] Bridge unit 2 has a reserved injection end with a diameter of 0.3 mm, which is connected to the main channel 9. Before injection, the injection end is connected to the vacuum device to evacuate the closed fluid chamber composed of the main channel 9, branch channel 10, through hole array 11 and transition layer hole 13, so that the vacuum degree in the chamber reaches -0.095 MPa and is maintained for 3 minutes.

[0056] After vacuuming is completed, with the sealed fluid chamber not connected to the outside air, the injection end is switched from the vacuum device to the injection device containing xanthan gum aqueous solution. The negative pressure in the sealed fluid chamber draws the xanthan gum aqueous solution into the main channel 9, branch channel 10, through-hole array 11, and transition layer pores 13.

[0057] After the xanthan gum aqueous solution is filled, the injection end is sealed with UV sealing glue 14 to isolate the closed fluid chamber from the oral cavity environment.

[0058] This embodiment also provides a dental restoration system. The dental restoration system includes a gradient stiffness load-bearing part, a pneumatic damping energy dissipation part, a microfluidic pressure regulation part, and a rigid-flexible coupling adapter part.

[0059] The gradient stiffness bearing component includes a retainer 1, a hexagonal honeycomb lattice in region A, a tetrahedral lattice in region B, and a dual-scale hybrid lattice in region C. The aerodynamic damping energy dissipation component includes an airflow channel 8. The microfluidic pressure regulation component includes a longitudinal groove 4, a main channel 9, branch channels 10, an array of through holes 11, transition layer pores 13, and a non-Newtonian shear-thinned fluid. The rigid-flexible coupling adaptation component includes a three-dimensional anatomical adaptation bottom surface 3 and a flexible transition layer 12.

[0060] Under the action of interlocking load, the hexagonal honeycomb lattice 5 in region A, the tetrahedral lattice 6 in region B, and the dual-scale hybrid lattice 7 in region C jointly bear the load, and adjust the load transfer path according to the different filling density and cell size of each region.

[0061] When controlled deflection occurs in the central region of bridge unit 2, the xanthan gum aqueous solution in the microfluidic network is compressed. As the shear rate increases, the apparent viscosity of the xanthan gum aqueous solution decreases, and the fluid is diverted from the main channel 9 to the six branch channels 10, and then enters the transition layer pores 13 through the through-hole array 11, causing local micro-deformation of the flexible transition layer 12 and dispersing the contact pressure in the central region to the cheek and tongue sides.

[0062] When the meshing vibration is transmitted to the C-region dual-scale mixed lattice 7, the gas in the gas flow channel 8 undergoes periodic compression, expansion and reciprocating flow, and consumes part of the vibration energy through viscous friction, compression hysteresis and heat exchange.

[0063] The flexible transition layer 12 is located between the zirconia pontoon unit 2 and the alveolar ridge mucosa. While adapting to the surface morphology of the alveolar ridge, it reduces the modulus difference between the rigid pontoon and the soft tissue.

[0064] After the occlusal load is removed, the hexagonal honeycomb lattice 5 in region A, the tetrahedral lattice 6 in region B, and the dual-scale hybrid lattice 7 in region C recover their elasticity, and the flexible transition layer 12 simultaneously resets. The area containing the pores 13 in the transition layer returns to its original shape and pushes the xanthan gum aqueous solution back to the branch channels 10 and the main channel 9 through the through-hole array 11. As the fluid shear rate decreases, the apparent viscosity of the xanthan gum aqueous solution increases, and the dental restoration system returns to its pre-load state.

[0065] This embodiment uses a six-unit posterior fixed bridge as an example. The six-unit posterior fixed bridge includes two retainers 1 and a bridge body unit 2 located between the two retainers 1, continuously covering four edentulous units.

[0066] First, intraoral scan data and cone-beam computed tomography (CBCT) data of the patient's edentulous area, abutment teeth, and alveolar ridge were acquired. Point cloud processing software was used to extract the alveolar ridge vertex cloud from the CBCT images and fitted to form a three-dimensional alveolar ridge crest line.

[0067] The baseline surface is formed by fitting the three-dimensional alveolar ridge crest line, the buccal mucosa inflection point and the lingual mucosa inflection point, and then a three-dimensional anatomical adaptation surface is established based on the surface morphology of the patient's alveolar ridge mucosa.

[0068] Subsequently, a fixation body 1 and a bridge body unit 2 are created in the 3D modeling software. The 3D anatomical adapter bottom surface 3 is imported into the bridge body unit 2, and a longitudinal groove 4, a main channel 9, six branch channels 10 and a through hole array 11 are created in the central area of ​​the 3D anatomical adapter bottom surface 3.

[0069] In the lattice design software, a hexagonal honeycomb lattice 5 for region A, a tetrahedral lattice 6 for region B, and a dual-scale hybrid lattice 7 for region C are generated respectively, and each region is set according to the aforementioned structural filling density, cell size, and span range.

[0070] Two hexagonal honeycomb lattices 5 in region A are respectively established in the connection region between the two retainers 1 and the bridge unit 2. Two tetrahedral lattices 6 in region B are respectively established in the near-middle quarter-span region and the far-middle quarter-span region of the bridge unit 2. A dual-scale hybrid lattice 7 in region C is established in the central half-span region of the bridge unit 2.

[0071] Cylindrical sacrificial channel models with a diameter of 0.2 mm are arranged inside the dual-scale hybrid lattice 7 in region C. The sacrificial channel models form a 7° angle with the near-far-mid span direction of the bridge unit 2. The center-to-center spacing between adjacent sacrificial channels is 1.08 mm, and they are offset by 0.1 mm in the height direction.

[0072] Multiple cylindrical sacrificial channel models are interconnected at their ends. The proximal and distal ends of the sacrificial channel models extend to the lingual non-occlusal surface of the pontoon unit 2, respectively, forming a cleaning inlet and a cleaning outlet that communicate with the outside.

[0073] The main bridge structure model and the sacrificial channel model were exported as dual-material models. The main bridge structure was manufactured using 3Y-TZP ceramic slurry, while the sacrificial channel was manufactured using photocurable water-soluble PVA material.

[0074] A dual-material photopolymer additive manufacturing system was used to simultaneously print the bridge body and the sacrificial channel. The system performed layer-by-layer exposure according to the bridge body model and the sacrificial channel model, and formed the 3Y-TZP ceramic slurry area and the water-soluble PVA material area respectively within the same layer.

[0075] Pre-curing is performed using 365nm ultraviolet light during the printing process, with a pre-curing energy of 120mJ / cm². 2 The thickness of the printed layer on the ceramic body is 25μm.

[0076] After printing, the bridge blank is placed in a 40℃ environment for pre-drying for 2 hours.

[0077] After pre-drying, the bridge body green body is immersed in deionized water at 37°C, allowing the deionized water to enter the sacrificial channel through the cleaning inlet, and the dissolved PVA material to be discharged through the cleaning outlet. The dissolution time of the PVA sacrificial channel is controlled between 42 and 47 minutes, and in this embodiment, the dissolution time is 45 minutes.

[0078] After the PVA sacrificial channels have dissolved, continue rinsing with 37°C deionized water from the cleaning inlet to the cleaning outlet until the liquid discharged from the cleaning outlet is free of visible PVA residue. After rinsing and drying, a continuous gas flow channel 8 is formed inside the dual-scale mixed lattice 7 in region C.

[0079] Subsequently, the bridge body green blank was degreased and sintered to obtain an integral zirconia bridge body.

[0080] After the zirconia bridge body is sintered, gas is introduced into the airflow channel 8 through the cleaning inlet, and the gas discharge is checked at the cleaning outlet to confirm that the airflow channel 8 remains connected.

[0081] After completing the connectivity test, UV sealing adhesive 14 is used to seal the cleaning inlet and cleaning outlet respectively, so that the airflow channel 8 forms an internally continuous and isolated pneumatic damping path from the oral cavity environment.

[0082] The dimensions of the hexagonal honeycomb lattice (5) in region A, the tetrahedral lattice (6) in region B, the dual-scale hybrid lattice (7) in region C, the airflow channel (8), the main channel (9), the branch channel (10), and the through-hole array (11) are all the final dimensions after the bridge body is sintered. When establishing the 3D model, dimensional compensation was performed based on the sintering shrinkage rate of the 3Y-TZP ceramic slurry used.

[0083] After the zirconia bridge body is manufactured, a flexible transition layer 12 is printed using TPU-based photosensitive resin, with a printing layer thickness of 50μm.

[0084] The flexible transition layer 12 forms transition layer holes 13 on the side facing the bridge unit 2. The flexible transition layer 12 is positioned on the three-dimensional anatomical adaptation bottom surface 3 so that it covers the bottom and surrounding area of ​​the longitudinal groove 4 and seals the groove openings of the main channel 9 and the branch channel 10, while the through hole array 11 is connected to the transition layer holes 13.

[0085] An incompletely cured TPU-based photosensitive resin is coated on the connection area of ​​the zirconia bridge body, and then the connection area is irradiated with ultraviolet light to cure the TPU-based photosensitive resin, and the flexible transition layer 12 is fixed to the zirconia bridge body.

[0086] After the flexible transition layer 12 is connected, a xanthan gum aqueous solution with a mass fraction of 0.8% is injected into the microfluidic network through the injection end with a diameter of 0.3 mm reserved in the bridge unit 2.

[0087] Before injection, connect the injection end to the vacuum device, evacuate the sealed fluid chamber to a vacuum level of -0.095MPa, and maintain the pressure for 3 minutes.

[0088] After the pressure holding is completed, in a closed fluid chamber that is not connected to the outside air, the injection end is switched to the liquid injection device, and the xanthan gum aqueous solution is drawn into the main channel 9, branch channel 10, through hole array 11 and transition layer hole 13 by using the negative pressure inside the chamber.

[0089] After filling, the injection end is sealed with UV sealing glue 14 to obtain the dental restoration system.

[0090] A vertical load of 200N was applied to the above six-unit posterior fixed bridge using finite element analysis software.

[0091] Under the same external morphology, load location, and boundary conditions, the bridge structure of this embodiment is compared with that of a traditional solid bridge. Simulation results show that the maximum deflection in the central region of bridge unit 2 in this embodiment is 19 μm, while the maximum deflection in the central region of a traditional solid bridge is 47 μm. The standard deviation of the contact pressure on the three-dimensional anatomical fit bottom surface 3 is reduced by 63%, and the maximum contact pressure is reduced from 2.8 MPa to 1.1 MPa.

[0092] In microfluidic pressure regulation tests, occlusal loading caused the xanthan gum aqueous solution to be diverted to both sides of the buccal and lingual sides along the main channel 9 and branch channels 10, resulting in a 41% decrease in the peak stress in the central region of the longitudinal groove 4. At 0.5 Hz and 10 Hz... 4 After one dynamic engagement cycle, the fluid pressure redistribution capability is maintained at a rate greater than 94%.

[0093] After the airflow channel 8 is formed, the material usage of the dual-scale hybrid lattice 7 in region C is reduced by 31%, and the printing time per piece is shortened by 22%.

[0094] In the vibration test, the two fixed bodies 1 of the bridge structure were fixed, and a sweeping vibration load was applied to the central region of the bridge unit 2. The test results showed that the main response frequency of the gas movement in the airflow channel 8 was 124Hz to 138Hz, and it was able to attenuate the biting impact energy in the frequency band of 110Hz to 150Hz.

[0095] See attached document Figure 6 This embodiment also provides an oral restoration method based on the above-described bridging structure and dental restoration system. The method includes digital modeling, gradient structure design, additive manufacturing, and microfluidic assembly, specifically comprising the following steps.

[0096] S100: Acquire intraoral scan data and cone-beam computed tomography (CBCT) data of the edentulous area, abutment teeth, and alveolar ridge of the patient. Register the two types of data to establish a three-dimensional oral model of the edentulous area. Based on the three-dimensional oral model, determine the morphology of the two retainers 1, pontoon unit 2, and three-dimensional anatomical adapter base 3, and establish a longitudinal groove 4 in the central region of the three-dimensional anatomical adapter base 3.

[0097] S200, hexagonal honeycomb lattices 5 are established in region A in the connection area between the two retainers 1 and the bridge unit 2; tetrahedral lattices 6 are established in region B in the near-middle quarter-span region and the far-middle quarter-span region of the bridge unit 2; and a dual-scale hybrid lattice 7 is established in region C in the central half-span region of the bridge unit 2. A gradient stiffness load-bearing structure is formed according to the filling density and cell size of each region.

[0098] Simultaneously, a sacrificial channel model corresponding to the tilted, misaligned, and interconnected airflow channels 8 is established within the dual-scale hybrid lattice 7 in region C. The two ends of the sacrificial channel model extend to the tongue-side non-engaging surface of the bridge unit 2, forming a cleaning inlet and a cleaning outlet. A main channel 9, six branch channels 10, and a through-hole array 11 are established at the bottom of the longitudinal groove 4.

[0099] The S300 uses a dual-material photocurable additive manufacturing system. It uses 3Y-TZP ceramic slurry to manufacture the stabilizer 1, bridge unit 2 and internal lattice, and uses photocurable water-soluble PVA material to manufacture the sacrificial channel corresponding to the airflow channel 8.

[0100] After printing, the bridge blank is pre-dried in an environment of 40°C for 2 hours, and then immersed in deionized water at 37°C. The deionized water enters the sacrificial channel from the cleaning inlet, and the dissolved PVA material is discharged from the cleaning outlet.

[0101] The dissolution time of the PVA material is controlled between 42 and 47 minutes, and the dissolution time in this embodiment is 45 minutes. After the PVA material is removed, internally rinsed and dried, the bridge body green body is degreased and sintered to form a continuous airflow channel 8 inside the dual-scale mixed lattice 7 in region C.

[0102] UV sealing adhesive 14 is used to seal the cleaning inlet and outlet, thus isolating the airflow channel 8 from the oral cavity environment.

[0103] S400 uses TPU-based photosensitive resin to manufacture a flexible transition layer 12, and forms transition layer holes 13 on the side of the flexible transition layer 12 facing the bridge unit 2.

[0104] The flexible transition layer 12 is applied to the bottom and surrounding area of ​​the longitudinal groove 4, thereby sealing the openings of the main channel 9 and the branch channel 10, and connecting the through-hole array 11 with the corresponding holes 13 in the transition layer. The flexible transition layer 12 is then fixed to the zirconia bridge body via UV curing.

[0105] The S500 uses an injection end with a diameter of 0.3 mm to evacuate a sealed fluid chamber to a vacuum level of -0.095 MPa and maintains the pressure for 3 minutes.

[0106] With the sealed fluid chamber not connected to the outside air, the injection end is switched to the liquid injection device. Using the negative pressure inside the sealed fluid chamber, a xanthan gum aqueous solution with a mass fraction of 0.8% is injected into the sealed fluid chamber, which is composed of the main channel 9, branch channel 10, through hole array 11 and transition layer hole 13.

[0107] After filling, UV sealing adhesive 14 is used to seal the injection end, forming a dental restoration system.

[0108] Working principle: When the dental restoration system is installed and bears the occlusal load, the occlusal load is first applied to the occlusal bearing surface of the pons unit 2. The load acting on the central region of the pons unit 2 is transferred to the tetrahedral lattice 6 in the B region on both sides through the dual-scale hybrid lattice 7 in the C region, and then to the abutment teeth on both sides of the edentulous area through the hexagonal honeycomb lattice 5 in the A region and the retainer 1.

[0109] Under the action of interlocking load, the central region of bridge unit 2 undergoes controlled elastic deflection, subjecting the xanthan gum aqueous solution in the sealed fluid chamber to transient pressure. The apparent viscosity of the xanthan gum aqueous solution decreases under high shear rate conditions, and it is diverted from the main channel 9 to the six branch channels 10, and then enters the corresponding transition layer pores 13 through the through-hole array 11.

[0110] The xanthan gum aqueous solution entering the transition layer pore 13 applies pressure to the continuous flexible material wall below the transition layer pore 13, causing elastic micro-deformation of the flexible material wall and dispersing the contact pressure in the central region of the bridge unit 2 to both sides of the cheek tongue. The biting vibration is simultaneously transmitted to the airflow channel 8 inside the C-region dual-scale mixed lattice 7. The gas in the airflow channel 8 undergoes compression, expansion, and reciprocating flow, and some of the vibrational energy is consumed through viscous friction between the gas and the inner wall of the channel, gas compression hysteresis, and heat exchange between the gas and the channel wall.

[0111] After the interlocking load is removed, the hexagonal honeycomb lattice 5 in region A, the tetrahedral lattice 6 in region B, and the dual-scale hybrid lattice 7 in region C recover to their pre-loaded state through their own elasticity, and the flexible transition layer 12 is simultaneously reset.

[0112] When the flexible transition layer 12 is reset, reverse pressure is generated inside the transition layer pores 13, pushing the xanthan gum aqueous solution back to the branch channel 10 through the through-hole array 11, and then back to the main channel 9 from the branch channel 10. As the fluid shear rate decreases, the apparent viscosity of the xanthan gum aqueous solution increases, and the dental restoration system returns to its pre-load state.

[0113] The three-dimensional anatomical adaptation base surface 3 is used to adapt to the anatomical morphology of the patient's alveolar ridge. The hexagonal honeycomb lattice 5 in area A, the tetrahedral lattice 6 in area B, and the dual-scale hybrid lattice 7 in area C are used to form a gradient stiffness load-bearing structure. The main channel 9, branch channels 10, through-hole array 11, transition layer pores 13, and non-Newtonian shear-thinning fluid are used to adjust the contact pressure between the pontoon unit 2 and the alveolar ridge mucosa. The airflow channel 8 is used to dissipate some of the occlusal vibration energy. The flexible transition layer 12 is used to adapt to the alveolar ridge mucosal surface and buffer the modulus difference between the zirconia pontoon unit 2 and the alveolar ridge mucosa.

[0114] The design and manufacturing process of the above structure includes, in sequence, digital modeling, gradient lattice design, dual-material additive manufacturing, sacrificial material dissolution and removal, ceramic degreasing and sintering, airflow channel sealing, flexible transition layer assembly, and negative pressure injection. When the dental restoration system is subjected to occlusal loads, it completes load transfer, fluid pressure distribution, and vibration dissipation; after the load is removed, the lattice structure, flexible transition layer 12, and xanthan gum aqueous solution return to their pre-loaded state.

Claims

1. A bridge structure, characterized in that, It includes a retainer (1) and a bridge unit (2), the retainer (1) being connected to the bridge unit (2), and the internal structure of the bridge unit (2) being divided into the following sections along the mesiodistal direction: The A-region hexagonal honeycomb lattice (5) is located at both ends, the B-region tetrahedral lattice (6) is located in a quarter-span region adjacent to the A-region hexagonal honeycomb lattice (5), and the C-region dual-scale hybrid lattice (7) is located in the central region. The C-region dual-scale hybrid lattice (7) is provided with multiple airflow channels (8). The bridge unit (2) is provided with a main road (9), and three branch roads (10) are provided on each side of the main road (9). The lower end of the bridge unit (2) is provided with a three-dimensional anatomical adaptation bottom surface (3). The lower end of the three-dimensional anatomical adaptation bottom surface (3) is provided with a longitudinal groove (4). The bottom of the longitudinal groove (4) is provided with an array of through holes (11). The bottom of the three-dimensional anatomical adapter (3) is provided with a flexible transition layer (12) at the lower end and multiple transition layer holes (13) at the upper end. The flexible transition layer (12) covers the opening of the longitudinal groove (4) and the transition layer holes (13) correspond to the positions of the through hole array (11).

2. The bridge structure according to claim 1, characterized in that, The through-hole array (11) is connected to the main channel (9) and the branch channel (10) respectively. The lower end of the through-hole array (11) is coaxially connected to the multiple transition layer holes (13). The retainer (1) is connected to the bridge unit (2) through the hexagonal honeycomb lattice (5) in region A. One end of the main channel (9) forms an injection end, and the injection end is provided with UV sealing glue (14).

3. The bridge structure according to claim 2, characterized in that, The axes of the multiple airflow channels (8) are set at an angle to the near-far direction of the bridge body unit (2). The airflow channels (8) include multiple interconnected cylindrical channel segments, and adjacent cylindrical channel segments are connected at their ends to form a continuously extending airflow passage.

4. A dental restoration system, characterized in that, The bridge structure includes any one of claims 1 to 3, and further includes a non-Newtonian shear thinning fluid. The main channel (9), the branch channel (10), the through hole array (11), and the transition layer holes (13) of the bridge structure are interconnected to form a closed fluid chamber. The non-Newtonian shear thinning fluid is encapsulated inside the closed fluid chamber.

5. The dental restoration system according to claim 4, characterized in that, The flexible transition layer (12) of the bridge structure covers the bottom of the longitudinal groove (4) of the bridge structure. The flexible transition layer (12) is in close contact with the bottom surface of the longitudinal groove (4) around the opening of the through hole array (11), and the flexible transition layer (12) does not enter the through hole array (11), the main road (9) and the branch road (10).

6. The dental restoration system according to claim 5, characterized in that, The non-Newtonian shear thinning fluid is a xanthan gum aqueous solution, the transition layer pore (13) is a non-penetrating blind hole, and the end of the transition layer pore (13) away from the bridge body unit (2) of the bridge body structure is closed by the continuous material wall of the flexible transition layer (12). When the non-Newtonian shear thinning fluid is squeezed, it applies pressure to the continuous material wall, causing the flexible transition layer (12) to undergo micro-deformation.

7. A method for oral restoration, characterized in that, The dental restoration system according to any one of claims 4 to 6 comprises the following steps: Acquire patient data and establish a three-dimensional oral model to determine the morphology of the fixation body (1), the pontoon unit (2) and the three-dimensional anatomical adapter bottom surface (3), and establish a longitudinal groove (4) in the three-dimensional anatomical adapter bottom surface (3). Inside the bridge unit (2), a hexagonal honeycomb lattice (5) in region A, a tetrahedral lattice (6) in region B, and a dual-scale mixed lattice (7) in region C are divided and established. Inside the dual-scale mixed lattice (7) in region C, a sacrificial channel model corresponding to the airflow channel (8) is established. A main channel (9), a branch channel (10), and a through hole array (11) are established at the bottom of the longitudinal groove (4), and an injection end is formed at one end of the main channel (9); The retainer (1), the bridge unit (2) and the sacrificial channel model are manufactured using additive manufacturing equipment. After the sacrificial material of the sacrificial channel model is dissolved and removed, the airflow channel (8) is formed by degreasing and sintering. A flexible transition layer (12) and transition layer holes (13) on its surface are manufactured, and the flexible transition layer (12) is covered and fixed to the longitudinal groove (4) so ​​that the through hole array (11) is connected to the transition layer holes (13); Non-Newtonian shear-thinning fluid is injected into a closed fluid chamber consisting of the main channel (9), the branch channel (10), the through-hole array (11), and the transition layer holes (13) through the injection end, and then sealed.

8. The oral restoration method according to claim 7, characterized in that, In the steps of manufacturing the retainer (1), the bridge unit (2) and the sacrificial channel model, the retainer (1), the bridge unit (2) and the hexagonal honeycomb lattice (5) of region A, the tetrahedral lattice (6) of region B and the dual-scale mixed lattice (7) of region C are manufactured using ceramic slurry. The sacrificial channel model corresponding to the airflow channel (8) is manufactured using water-soluble material. The airflow channel (8) is formed by dissolving and discharging the water-soluble material through water injection.

9. The oral restoration method according to claim 7, characterized in that, In the step of manufacturing the flexible transition layer (12), the flexible transition layer (12) is printed using TPU-based photosensitive resin, and the incompletely cured TPU-based photosensitive resin is coated on the connection area between the bridge unit (2) and the flexible transition layer (12). The flexible transition layer (12) and the bridge unit (2) are fixed by curing with ultraviolet light.

10. The oral restoration method according to claim 7, characterized in that, In the step of injecting the non-Newtonian shear thinning fluid, before injecting the non-Newtonian shear thinning fluid, the sealed fluid chamber is first evacuated to a set negative pressure state through the injection end reserved in the main channel (9) and pressure is maintained. Then, the non-Newtonian shear thinning fluid is sucked into the sealed fluid chamber by the negative pressure inside the chamber.